Comprehensive Genetic Analysis of Pregnancy Loss by Chromosomal Microarrays: Outcomes, Benefits, and Challenges. Issue 5 (May 2017) - Sahoo, Trilochan; Dzidic, Natasa; Strecker, Michelle N.; Commander, Sara; Travis, Mary K.; Doherty, Charles; Tyson, R. Weslie; Mendoza, Arturo E.; Stephenson, Mary; Dise, Craig A.; Benito, Carlos W.; Ziadie, Mandolin S.; et al.
Abstract : (Abstracted from Genet Med 2017;19(1):83–89) High-resolution chromosomal microarray analysis (CMA) with single-nucleotide polymorphism (SNP)–based arrays is increasingly used for pediatric and prenatal diagnoses as they can simultaneously detect aneuploidies, submicroscopic chromosomal imbalances, triploidy, and regions of allelic homozygosity. Overall, 15% to 20% of clinically recognized pregnancies end in miscarriage, and approximately 1% of couples experience recurrent (at least 2) pregnancy losses.